“CURATORS OF MEMORY”: WOMEN’S VOICES IN LITERATURE IN ENGLISH - Redakcja (Wydział Anglistyki UAM, 2015)
The present volume of essays joins the literary and academic debate on the value and power of female voices in literature and beyond, offering a multifaceted selection of writerly and academic perspectives on themes, such as various types of femininities, Écriture féminine, storytelling and memory, gender and ethnic identity, socialisation of women, violence against, and by, women, female bodies, madness and hysteria, sexism and religion, etc. The essays collected in the present volume re-member historical/ actual and fictional women and their fate in various historical and literary periods, allowing the reader to see diachronic changes to the perception of femininity as well as writing by women.
Keywords: feminism; female writers; literature in English